Association between responsiveness to methoxy polyethylene glycol‐epoetin beta and renal survival in patients with non‐dialysis‐dependent chronic kidney disease: A pooled analysis of individual patient‐level data from clinical trials. Issue 10 (October 2017) - Tsuruya, Kazuhiko; Uemura, Yukari; Hirakata, Hideki; Kitazono, Takanari; Tsubakihara, Yoshiharu; Suzuki, Masashi; Ohashi, Yasuo
Abstract: Aim: The association between responsiveness to continuous erythropoietin‐receptor activator (CERA) and renal survival in patients with non‐dialysis‐dependent chronic kidney disease (NDD‐CKD) is uncertain. Methods: We performed a pooled analysis of individual patient‐level data drawn from five clinical trials involving CERA administration. Based on the responsiveness to CERA, patients were classified into poor‐ or good‐response groups. Primary endpoints were defined as the initiation of dialysis or a 30% decrease in the estimated glomerular filtration rate (eGFR) from baseline. We set the landmark time point at 12 weeks after the start of CERA, from which we evaluated the time to the first renal event. The cumulative renal survival rates were calculated for each group using the Kaplan–Meier method. The adjusted hazard ratio was calculated using a stratified Cox regression model. Results: Of 408 patients, 226 were analyzed. Haemoglobin levels and eGFRs were significantly lower in the poor‐response group ( n = 113) than in the good‐response group ( n = 113). Renal events occurred in 36.3% of the poor‐response group and in 23.0% of the good‐response group. The intergroup difference in renal survival rates was significant (log‐rank test, P = 0.03) and the adjusted hazard ratio was 1.71 (95% confidence interval, 1.03–2.83), indicating an unfavorable outcome in the poor‐response group. Conclusion: Hyporesponsiveness to CERA was associated with poor renal survival, consistent with the results of the conventional erythropoiesis‐stimulating agent (ESA). It is recommended that a randomized controlled trial on CERA use be performed in patients with NDD‐CKD with ESA‐hyporesponsive anaemia. Summary at a Glance: To elucidate the association between responsiveness to continuous erythropoietin‐receptor activator (CERA) and renal survival in patients with non‐dialysis‐dependent chronic kidney disease (NDD‐CKD), we performed a pooled analysis of individual patient‐level data drawn from five clinical trials involving CERA administration. Based on the responsiveness to CERA, patients were classified into poor‐ or good‐response groups. Occurrence of renal events was significantly higher in the poor‐response group than in the good‐response group. We confirmed that hyporesponsiveness to CERA was associated with poor renal survival, consistent with the results of conventional erythropoiesis‐stimulating agent.